Temporomandibular joint function 10-15 years after mandibular setback surgery and six weeks of intermaxillary fixation - Mohammedreza Sefidroodi; Ole Kristian Lobekk; Sigbjørn Løes; Elisabeth Schilbred Eriksen (Journal of Applied Oral Science)
Abstract Intermaxillary fixation (IMF) is a classic method for immobilization of the mandible after mandibular fractures and corrective surgery. However, it has been suggested that IMF may be a risk for developing temporomandibular joint (TMJ)-related symptoms, especially when applied for longer periods. Objective: To evaluate the clinical function of TMJs and masticatory muscles 10-15 years after mandibular setback surgery and subsequent six weeks of IMF. The patients' self-reported TMJ and masticatory muscle symptoms were also addressed. Methodology: Thirty-six patients (24 women and 12 men) treated with intraoral vertical ramus osteotomies and subsequent six weeks of IMF, underwent a clinical examination of TMJs and masticatory muscles 10-15 years after surgery and completed a five-item structured questionnaire reporting subjective TMJ-related symptoms. Mean age by the time of clinical examination was 34.1 years (range 27.2–59.8 years). The clinical outcome was registered according to the Helkimo clinical dysfunction index. Descriptive and bivariate statistics were performed and level of significance was set to 5%. Results: Mean maximum unassisted mouth opening 10-15 years after surgery was 50.1 mm, (range 38-70 mm, SE 1.2), statistically significantly greater in men compared to women (p=0.004). Mean Helkimo dysfunction group was 1.5 (range 1-3, SE 0.10). Eighty-one percent experienced pain on palpation in either the masseter muscle, temporal muscle or both, and 31% experienced pain when moving the mandible in one or more directions. Thirty-one percent reported pain from palpating the TMJs. In the questionnaire, none reported to have pain during chewing or mouth opening on a weekly or daily basis, but 22% reported difficulties with maximum opening of the mouth. Conclusion: Ten to fifteen years after mandibular setback surgery the patient's mandibular range of movement is good. Despite clinically recognizable symptoms, few patients reported having TMJ- or masticatory muscle-related symptoms in their daily life.